A comparison of commercial modified-live PRRSV-1 and PRRSV-2 vaccines against a dual heterologous PRRSV-1 and PRRSV-2 challenge in late term pregnancy gilts. (April 2020) - Yang, Siyeon; Oh, Taehwan; Cho, Hyejean; Chae, Chanhee
Highlights: Vaccination of gilts with PRRSV-1 MLV did not provide good protection against PRRSV-1 and PRRSV-2 challenge. Vaccination of gilts with PRRSV-2 MLV provided good protection against PRRSV-1 and PRRSV-2 challenge. Vaccination of gilts with PRRSV-2 MLV improved reproductive performance. Abstract: This study compared the efficacy, in terms of reproductive performance, of a porcine reproductive and respiratory syndrome virus (PRRSV)-1 or PRRSV-2 modified-live virus (MLV) vaccine against a dual heterologous PRRSV-1 and PRRSV-2 challenge. Gilts were administered either the PRRSV-1 or PRRSV-2 MLV vaccine at 21 days prior to breeding and were challenged intranasally with both PRRSV species at day 93 of gestation. Vaccination of gilts with PRRSV-2 MLV vaccine resulted in improved reproductive performance in sows (e.g. duration of pregnancy) and piglet health and overall viability (e.g. increase of the number of live-born and weaned pigs, and decrease of stillborn). Vaccination of gilts with PRRSV-1 MLV vaccine was able to reduce only PRRSV-1 viremia in contrast, PRRSV-2 MLV vaccine was able to reduce both PRRSV-1 and PRRSV-2 viremia. Vaccination of gilts with PRRSV-2 MLV induced higher numbers of PRRSV-2 specific interferon-γ secreting cells (IFN-γ-SC) compared to the PRRSV-1 MLV while there was no difference in the number of PRRSV-1 specific IFN-γ-SC between the two vaccines. Taken together, the results presented here suggest that vaccination of gilts with the PRRSV-2 MLV vaccine is more efficacious against dual heterologous PRRSV-1 and PRRSV-2 challenge compared to the PRRSV-1 MLV vaccine.